2014
DOI: 10.1038/bjc.2014.473
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin and non-steroidal anti-inflammatory drug use and the risk of upper aerodigestive tract cancer

Abstract: Background:Aspirin and other non-steroidal anti-inflammatory drugs (NSAIDs) are widely used as analgesics and preventative agents for vascular events. It is unclear whether their long-term use affects cancer risk. Data on the chemopreventative role of these drugs on the risk of the upper aerodigestive tract cancer (UADT) are insufficient and mostly refer to oesophageal cancer. The aim of this study was to investigate the effect of aspirin and other NSAIDs on the risk of UADT cancers.Methods:A nested case–contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 30 publications
(39 reference statements)
0
43
0
Order By: Relevance
“…10,11 In brief, PCCIU was founded in 1999 to feedback and are representative of the Scottish population with a similar spread of age, gender, material deprivation and rurality. 12 We carried out a retrospective analysis of PCCIU cohort; our population was all adults aged 16 years or older with an incident diagnosis of either heart failure or a cancer between 1 April 2002 and 31 st March 2011 (the last update of the PCCIU dataset).…”
Section: Study Design and Settingmentioning
confidence: 99%
“…10,11 In brief, PCCIU was founded in 1999 to feedback and are representative of the Scottish population with a similar spread of age, gender, material deprivation and rurality. 12 We carried out a retrospective analysis of PCCIU cohort; our population was all adults aged 16 years or older with an incident diagnosis of either heart failure or a cancer between 1 April 2002 and 31 st March 2011 (the last update of the PCCIU dataset).…”
Section: Study Design and Settingmentioning
confidence: 99%
“…Likewise, regular aspirin use (defined as at least once a week for 1 year) was associated to a borderline 13% risk reduction of upper aero-digestive tract cancer in the AlcoholRelated CAncer and GEnetic Susceptibility (ARCAGE) study [10]. A similar risk reduction was reported for NSAIDs use in upper aerodigestive tract cancer in a recent British case-control study [7]. Finally, aspirin use was inversely -though not significantly -associated with the risk of cancer of the upper aerodigestive tract in Italy (OR = 0.86) [5].…”
Section: Discussionmentioning
confidence: 61%
“…Studies on head and neck cancers and aspirin use are still scanty and with inconsistent results [5][6][7], and only few of them included NPC [2,6]. Therefore, to further evaluate the possible role of aspirin use on NPC risk in a low-incidence country, we analyzed data from a hospital-based case-control study conducted in Italy.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally statins inhibit proliferation and induce apoptosis in Barrett's cell lines and these effects are enhanced in an additive manner in combination with inhibition of the cyclo-oxygenase-2 pathway (10,11). Over-expression of COX-2 in Barrett's mucosa has been reported, and experimentally (34), and in clinical studies beneficial effects of COX-inhibitors on progression to cancer have been reported (13,16,(35)(36)(37). Thus it is possible that statin and aspirin impair survival of the Barrett's clone at a very early stage and so impair establishment of a mature Barrett's segment.…”
Section: Discussionmentioning
confidence: 99%